Epilepsy surgery in patients older than 50 years: Effectiveness, safety, and predictors of outcome. (August 2017) - d' Orio, Piergiorgio; Pelliccia, Veronica; Gozzo, Francesca; Cardinale, Francesco; Castana, Laura; Lo Russo, Giorgio; Bottini, Gabriella; Scarpa, Pina; Cossu, Massimo
Highlights: Epilepsy surgery has the same effectiveness in younger and older patients. Risk of surgical complications is higher in patients older than 50 years. Preoperative high seizure frequency and LEAT etiology predict poor seizure outcome. No changes of preoperative cognitive performances were evidenced postoperatively. Patients older than 50 years could experience an improvement of mood after surgery. Abstract: Purpose: Surgery is an effective treatment for drug resistant focal epilepsy. Predictors of seizure outcome have been extensively addressed in the general population but similar data on older patients are still lacking. The aim of this study is to evaluate effectiveness and safety of surgery for patients over 50 years and to investigate variables associated to seizure outcome. Methods: We performed a single center retrospective study including 50 patients over 50 years treated surgically for drug resistant focal epilepsy between 1997 and 2014. We analyzed the rate of success of seizure control, the association of several clinical variables with seizure outcome and the rate of surgery-related complications. We also investigated the impact of surgery on the patients' cognitive performances and mood profile. Results: At last follow-up 78% of our patients were seizure-free, similar to patients younger than 50 years operated on in the same period (p = 1). The rate of surgery-related complications was 10%, higher compared to younger patients (p < 0.0001). Pre-surgical daily seizure frequency (p = 0.0040) and the histological diagnosis of LEAT (p = 0.0233) were associated to a poorer seizure outcome. No significant differences were evidenced between pre- and postoperative neuropsychological profiles. A slight, not statistically significant improvement of the mood profile was observed postoperatively. Conclusion: Our results suggest that surgery is an effective treatment option also for older epileptic patients, although it is burdened by a higher surgical risk as compared to younger patients. The availability of predictors of outcome also for these patients may be helpful for pre-surgical counseling.